HUBUNGAN TINGKAT STRES DAN POLA MAKAN DENGAN KEJADIAN HIPERTENSI DALAM KEHAMILAN DI PUSKESMAS SIMPANG IV SIPIN KOTA JAMBI - Ditatri Utami; Sri Mulyani; Yulia Indah Permata Sari; Nurhusna; Putri Irwanti Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Background: Hypertension in pregnancy is one of the main causes of maternal and perinatal morbidity and mortality. Psychological factors such as stress and lifestyle factors such as diet are known to play a role in increasing the risk of hypertension during pregnancy. Objective: To determine the relationship between stress levels and diet with the incidence of hypertension in pregnancy at Simpang IV Sipin Community Health Center, Jambi City. Method: Quantitative research with a cross-sectional design. The study sample consisted of 96 pregnant women in the second and third trimesters selected using a total sampling technique. Stress levels were measured using the DASS-42 questionnaire, diet was measured using a structured questionnaire, and blood pressure was classified into Grade 1, 2, and 3 hypertension. Data analysis was performed using the Spearman Rank correlation test with a significance level of α = 0.05. Results: Most respondents experienced mild stress (70.8%), had a good diet (54.2%), and had Grade 1 hypertension (88.5%). Spearman's test results showed a strong and significant relationship between stress levels and the incidence of hypertension (rs = 0.691; p < 0.001), as well as a moderate and significant relationship between diet and the incidence of hypertension (rs = 0.386; p < 0.001). Conclusion: Stress levels and diet are significantly associated with the incidence of hypertension in pregnancy. Stress screening and nutrition education are needed as part of antenatal care.